2020
DOI: 10.1016/j.energy.2020.118695
|View full text |Cite
|
Sign up to set email alerts
|

Improved bi-functional oxygen electrocatalytic performance of Pt–Ir alloy nanoparticles embedded on MWCNT with Pt-enriched surfaces

Abstract: Multi-walled carbon nanotube supported PteIr nanoparticles (PteIr/MWCNT) with different elemental ratios were synthesized by one-pot co-reduction approach under ambient conditions. The PteIr catalysts exhibit improved bi-functional activity towards oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) and its electrocatalytic performance was clearly established using different physiochemical characterization techniques. The PteIr composition of 2:1 has a higher electrochemical surface area (ECSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…Because the bonding of H ad to the Pt and Ir surfaces is considered to be stronger compared with that for optimal HOR activity enhancement, 31,32 appropriately weakened H ad bonding would show maximum HOR activity for Pt x ML /Ir(111). According to the literature, the coexistence of Pt and Ir can result in interatomic charge transfer 13,33 and this is consistent with the chemical shift of Pt4f observed in the present study (Fig. S.2, ESI.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Because the bonding of H ad to the Pt and Ir surfaces is considered to be stronger compared with that for optimal HOR activity enhancement, 31,32 appropriately weakened H ad bonding would show maximum HOR activity for Pt x ML /Ir(111). According to the literature, the coexistence of Pt and Ir can result in interatomic charge transfer 13,33 and this is consistent with the chemical shift of Pt4f observed in the present study (Fig. S.2, ESI.…”
supporting
confidence: 93%
“…Also, the value of i T /| i S | for Pt 0.3ML /Ir(111) (blue) remained almost at the noise level below 0.2 V, though i T /| i S | slightly increased in E S > 0.2 V. In contrast, the value of i T /| i S | for Pt 0.5ML /Ir(111) (red) exhibited marked H 2 O 2 generation throughout the potential range of 0.06–0.3 V. The results indicate that the value of x (Pt-deposited thicknesses) less than 0.5 ML for Pt x ML /Ir(111) tends to suppress the H 2 O 2 generation in the potential region of <0.2 V, which seems consistent with several studies reported for H 2 O 2 generation through ORR on the Pt–Ir catalysts with Pt-enriched surfaces. 33,38,39 The present study revealed that the Ir-enriched surfaces of Ir–Pt bimetallic materials, contrary to the Pt-enriched surfaces, are effective in mitigating the H 2 O 2 generation.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…[1][2][3] The hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), and oxygen evolution reaction (OER) are the core reactions of the systems mentioned above, and high-efficiency catalysts are required to accelerate the rate of these reactions. [4][5][6][7][8][9][10] Precious metal [11][12][13] and metal oxide materials 14,15 have long been used as efficient electrocatalysts for the HER/ORR/OER. However, their high cost and scarcity limit the large-scale application of renewable energy technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the as-synthesized Pt–Ir alloys display a poor bifunctional activity toward ORR and OER relative to pure Pt and Ir. Xu et al further studied the composition-dependent bifunctional activity of Pt–Ir alloys on carbon nanotubes fabricated by one-pot co-reduction and found that the high proportion of stable IrO x species on Ir surface would decay ORR activity, while the presence of the Pt component can seriously weaken the OER, thereby resulting in a poor bifunctional performance . Another strategy to address the above issue may be nanophase engineering of active Pt and Ir parts to form a reasonable phase structure with double active sites for ORR and OER, respectively .…”
Section: Introductionmentioning
confidence: 99%